Transition-Metal-Catalyzed Synthesis of 1,3-Diynes and Ynamides from 2-Bromo-1-iodoalkenes - Xue, Jun; Luo, Miao-Ting; Wen, Yue-Lu; Ye, Min; Liu, Liang-Xian; Chen, Zheng-Wang (Synthesis, 2014)
Diynes and ynamides are important products in chemical synthesis. An efficient palladium-catalyzed homocoupling reaction of 2-bromo-1-iodoalkenes to give 1,3-diynes has been developed. The reactions are conducted under convenient conditions and provide products in moderate to excellent yields. Moreover, ynamides were synthesized from 2-bromo-1-iodoalkenes and carbamates, and it is noteworthy that this reaction is catalyzed by nanoparticulate copper(I) oxide to give ynamides in high yields.
Keywords: catalysis; palladium; copper; alkynes; amides; coupling